(untitled) (Journal of Scientific Research, 2024)
When the source for the energy-momentum tensor is a bulk viscous fluid containing one-dimensional cosmic strings, a spatially homogeneous and anisotropic Bianchi type-V cosmological model is considered in this paper in a scalar-tensor theory of gravitation proposed by Saez-Ballester, we derive a determinate solution utilizing the plausible physical conditions: (i) the scalar of spacetime expansion is proportional to the shear scalar; (ii) the baratropic equation of state for pressure and density; and (iii) the bulk viscous pressure is related to the energy density. The model’s physical and kinematic features are also discussed.